Europejski sektor MSP wobec wyzwań globalizacji - Daszkiewicz, Nelly (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The last decade has been the period of tremendous changes in the world economy, caused to great extent, by globalization and diffusion of Information and Communication Technologies (ICT). These processes have dramatically changed conditions of functioning of SMEs. They have created both new opportunities for expansion towards new market and threats resulting from the increase of competition. Global economy requires the improvement of competitiveness of European SMEs that, in turn, implies changes in economic policy. The purpose of this article is to point at the requirements of globalization towards European SMEs and analyses of the factors that increase their competitiveness. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1173, s. 70-77